Ultrasonic vibration assistance in shear cutting of electrode materials for lithium-ion batteries. (January 2015) - Roscher, H.-J.; Ebert, L.; Roscher, M.A.; Hielscher, H.
Abstract: The electrodes of today's lithium-ion cells are produced as a compound made of copper or aluminium foil several micrometres thick. This film functions as a conductor and is coated on both sides with an active material with the capacity to store energy. In battery production, shaping by shear cutting of these planar electrodes is an essential stage in the process chain. However, advanced techniques established in mass production, such as laser cutting and water jet cutting, are not always suitable for the manufacturing process particularly in case of avoiding thermal and chemical impact on the composite material. Conventional shear cutting (fine shear cutting) is also problematic, since the very thin film makes for very tight clearances. One way to circumvent the problems in shear cutting described above results from superposing the punch with vibrations. In the example described in the paper, frequencies from 20 to 40 kHz at vibration amplitudes greater than 3 μm were used. It was recognised that superposition of vibrations enhances breakage at the cutting edge and, consequently, reduces formation of flash on the electrode contour.